The Application of Numerical Ductile Fracture Simulation in the LBB Evaluation of Nuclear Pipes - Yuxuan Fang; Biao Li; Chang-Sung Seok; Tao Shen (Applied Sciences)
The leak-before-break (LBB) concept is widely used in the design and estimation of piping systems of nuclear power plants, which requires considerable test work to obtain the fracture resistance (J-R) curves of nuclear pipes. The application of numerical ductile fracture simulation can effectively limit the test work. In this study, an extended stress-modified critical strain (SMCS) model is applied to simulate the crack growth behaviors of full-scale nuclear pipes (SA312 TP304L stainless steel) with a circumferential through-wall crack under a four-point bending load. The LBB evaluation is performed based on the J-R curves of CT specimens and full-scale pipes obtained from fracture resistance tests and numerical simulations. It shows that due to the high crack-tip constraint effect, CT specimens may cause lots of conservatism in the LBB evaluation of nuclear pipes, while the application of numerical ductile fracture simulation can largely reduce the conservatism.